Linking Global CGE models with Sectoral Models to Generate Baseline Scenarios: Approaches, Challenges, and Opportunities - Ruth Delzeit; Robert Beach; Ruben Bibas; Wolfgang Britz; Jean Chateau; Florian Freund; Julien Lefevre; Franziska Schuenemann; Timothy Sulser; Hugo Valin; Bas van Ruijven; Matthias Weitzel; et al. (Journal of Global Economic Analysis, 2020)
When modeling medium and long-term challenges we need a reference path of economic development (the so-called baseline). Because sectoral models often offer a more fundamental understanding of future developments for specific sectors, many CGE modeling teams have adopted approaches for linking their models to sectoral models to generate baselines. Linked models include agricultural sector, energy sector, biophysical and macroeconomic models. We systematically compare and discuss approaches of linking CGE models to sectoral models for the baseline calibration procedure and discuss challenges and best practices. We identify different types of linking approaches which we divide into a) one-way, and b) twoway linking. These two types of linking approaches are then analyzed with respect to the degree of consistency of the linkage, information exchanged, as well as compromises in aggregations and definitions. Based on our assessment, we discuss challenges and conclude with suggestions for best practices and research recommendations.
Keywords: C68; D58; 330; Computable general equilibrium models; Model linking baseline scenario; Partial equilibrium model